Propriété antioxydante du chitosane issu des carapaces de crustacés (crevettes) - DAHMENE, RYAD; ELAHOUEL, Abderrahmen (My University, 2020)
The objective of this study is to try to determine the antioxidant activity of chitosan obtained from shrimp shells and this after having extracted this polymer by a chemical process, carried out in 4 stages (demineralization, deproteinization, bleaching and deacetylation). The antioxidant power of chitosan prepared at different concentrations will be evaluated in vitro by the free radical scavenging test (DPPH) and the test of total antioxidant activity. Here, Ascorbic acid and BHA will be used as positive comparison controls. However, the state of containment linked to the (Covid - 19) pandemic, caused the experiment to be canceled and will be replaced by the study of a few scientific articles related to the theme. The results found in these articles and proven by the various tests carried out, have shown that chitosan has significant antioxidant activity, but which depends on its molecular weight and the degree of deacetylation of the molecule. In comparison with the positive free radical scavenger controls (DPPH), it is still lower. With his antioxidant activity, Chitosan can be used in several food applications, either as an additive or as an edible film.
Keywords: Shrimp shells; Chitosan; Antioxidant Activity; DPPH; Ascorbic acid; BHA